Evaluating the influence of Ti6Al4V alloy particles on mechanical properties of heat-cured PMMA - AlFuraiji , Nihad H; Altaie , Shurooq F; Qasim, Syed S (Journal of Baghdad College of Dentistry, 2024)
Background: Titanium alloy (Ti6Al4V) is considered a promising material for prosthetic dental applications due to its superior density, high strength, improved corrosion resistance and superior biocompatibility. Due to the low strength and brittleness of the practicable denture foundation material in heat-cured acrylic resin, improving the strength properties is a crucial issue. The present study aimed to evaluate the influence of Ti6Al4V alloy particles on the tensile strength transverse strength, and the surface hardness of heat-cured PMMA as a base material. Materials and methods: A total of 75 specimens were prepared by combining heat-cured acrylic resin with Ti6Al4V additive particles (0.5, 1, 1.5, and 2 wt. % respectively). Each group was subdivided into three subgroups according to the samples subjected to the test (n = 25), tensile strength; transverse strength; and surface hardness. Results: The result showed a significant difference (P= 0.007) in all tested groups. The results showed that the addition of Ti6Al4V particles to heat-cured material considerably increased the tensile strength, transverse strength, and surface hardness-a compared to the untreated control specimens. Conclusion: It was found that increasing the weight concentration (wt.) of Ti6Al4V particles improved the tensile strength, transverse strength, and surface hardness of heat-cured PMMA specimens.